2022
DOI: 10.3390/metabo12080726
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Urinary Biomarkers of Antipsychotic-Induced Metabolic Syndrome

Abstract: Metabolic syndrome (MetS) is a clustering of at least three of the following five medical conditions: abdominal obesity, high blood pressure, high blood sugar, high serum triglycerides, and low serum high-density lipoprotein (HDL). Antipsychotic (AP)-induced MetS (AIMetS) is the most common adverse drug reaction (ADR) of psychiatric pharmacotherapy. Herein, we review the results of studies of blood (serum and plasma) and urinary biomarkers as predictors of AIMetS in patients with schizophrenia (Sch). We review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 283 publications
0
36
0
Order By: Relevance
“…One study reported elevated levels even in first‐onset patients with schizophrenia 65 . Although the FGF system is considered a potential target in schizophrenia, 66 there are no data on the effect of antipsychotics on FGF‐21 67 . FGF‐21, as a mediator of energy homeostasis, represents a target for emerging new potentially beneficial therapies for obesity, dyslipidemia, and glucose dysregulation 68–70 and possibly in the development of strategies in prevention or treatment of adverse metabolic effects of antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported elevated levels even in first‐onset patients with schizophrenia 65 . Although the FGF system is considered a potential target in schizophrenia, 66 there are no data on the effect of antipsychotics on FGF‐21 67 . FGF‐21, as a mediator of energy homeostasis, represents a target for emerging new potentially beneficial therapies for obesity, dyslipidemia, and glucose dysregulation 68–70 and possibly in the development of strategies in prevention or treatment of adverse metabolic effects of antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced level of central serotonin is consistently linked to heightened impulsivity [24]. In obese individuals, insulin resistance is associated with elevated postprandial free fatty acid (FFA) level [25]. These FFAs compete with tryptophan, the precursor of serotonin, for binding to serum albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic drugs are the main form of treatment for schizophrenia, and long-term maintenance antipsychotic treatment can protect against all-cause mortality (RR = 0.71, 95% CI: 0.59-0.84, n = 11) compared with no use of anti-psychotics [4]. However, almost all antipsychotic drugs lead to the development of metabolic syndrome (MetS) [5].…”
Section: Introductionmentioning
confidence: 99%